Model Determining the Success of Sustainability Report Disclosure in Indonesia - Triyono; Fatchan Achyani; Sandy Prasetyo; Lamin Khaira (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the effect of profitability, leverage, liquidity, company size, corporate governance, environmental performance, and media exposure on sustainability reports. The research method used is regression analysis with secondary data obtained from the Company's annual and sustainability reports, the Company Sample uses Mining Companies listed on the Indonesia Stock Exchange with a total sample of 110, for the period 2019-2023. The results of the study indicate that profitability, leverage, liquidity, company size, corporate governance, and environmental performance do not have a significant effect on sustainability reports. Meanwhile, media exposure has a significant effect on sustainability reports. This finding indicates that media publication and attention can encourage companies to be more transparent in their sustainability reporting. Novelty From this study This study highlights the importance of media exposure as an external factor that influences sustainability reports, which has not been widely studied in previous studies, The results show that companies are more motivated to disclose sustainability reports when they are in the spotlight from the media, indicating that transparency is not only driven by internal factors, but also external pressure